PENGARUH LITERASI DIGITAL TERHADAP KEMANDIRIAN BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Yusti Juliani; Etty Pratiwi; Mega Prasrihamni (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2026)
This study aimed to determine the influence of digital literacy on the self-directed learning of fifth-grade elementary school students as an effort to improve 21st-century learning, which emphasizes literacy skills and self-directed learning. The method used in this research is quantitative with a quasi-experimental approach. The independent variable of this study is the audio-visual media, while the dependent variable is the learning outcomes of IPAS. This research method employs a posttest control group design with a sample of students from the control and experimental classes, totaling 57 students. The results of the post-test data analysis show that the average score of the experimental group is 84.38, which is higher than the control class with an average score of 57.8. The analysis technique used in this study is the t-test, where the hypothesis testing yielded a t_calculated value of 17.317 < t_table, and also a t_calculated value of 2.004 < t_table. Based on the independent sample t-test in this study, the sig (2-tailed) value obtained is 0.000 < 0.05, so it can be concluded that the significant value is less than 0.05, hence Ho is rejected and Ha is accepted (there is an effect). Thus, the use of digital literacy media based on animated videos has been proven to significantly affect the improvement of learning independence in the IPAS subject for fifth-grade students at SDN 30 Palembang.